Slip Resistance (Friction) and Safe Walk Characteristics of Selected Shoe Soles on Floor Tiles in Nigeria (British Journal of Multidisciplinary and Advanced Studies, 2024)
Slip-related accidents represent a significant public safety concern, particularly in environments where flooring may be exposed to various contaminants. This research investigates the slip resistance characteristics of selected shoe soles on different types of local floor tiles, employing the British Pendulum Tester (BPT) under diverse conditions, including: dry, sandy, wet, soapy, and oily surfaces. The study aims to provide quantitative data on friction coefficients to comprehensively assess the performance of different shoe sole and tile combinations. The results indicate varying levels of slip resistance across the tested combinations, with some shoe soles demonstrating superior performance under specific conditions. For instance, Poly-Urethane soles consistently showed higher friction coefficients in both dry and contaminated conditions, suggesting their suitability for environments prone to slip hazards. Conversely, certain tiles exhibited lower slip resistance when exposed to water and oily substances, highlighting the need for careful selection of both footwear and flooring materials in safety-critical applications. The findings underscore the importance of considering environmental factors in evaluating footwear performance, providing practical implications for improving safety standards in public and private spaces. The data generated from this research can inform recommendations for better footwear design, floor tile selection, and maintenance practices to mitigate slip hazards effectively. This study emphasizes the significance of evidence-based approaches in enhancing slip resistance standards, advocating for ongoing research and industry collaboration to ensure continuous improvement in safety protocols.